The Relationship Between Vein Diameters, Clinical Severity, and Quality of Life: A Systematic Review. (June 2019) - Tan, Matthew K.H.; Sutanto, Sharon A.; Onida, Sarah; Davies, Alun H.
Abstract : Objective/background: The aim was to summarise the evidence for the relationship between vein diameters and clinical severity, and elucidate the relationship between diameters and health related quality of life (HRQoL) Methods: A systematic review was performed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines. The MEDLINE and Embase databases were searched from 1946 to 31 August 2018. Reference lists of included studies were searched for further relevant papers. Full text studies in English reporting the relationship between great and small saphenous vein diameters and clinical severity and/or HRQoL scores measured using validated instruments were included. All study designs were included. Studies that did not include relationships between these parameters, non-English studies, and studies focusing on non-truncal veins were excluded. Two reviewers independently performed the study selection, data extraction, and risk of bias assessment. Results: Eleven eligible studies were identified, reporting on 2, 732 limbs (range 22–681). Four studies correlated truncal vein diameter with both clinical severity and HRQoL, while seven reported only on clinical severity measures. Multiple instruments were used to quantify HRQoL and clinical severity. Seven studies assessed the relationship with CEAP class, with the majority observing a positive correlation between vein diameter and disease severity. Four studies found weak correlations with VCSS, with one showing correlations with VCSS components. No significant relationship between diameters and HRQoL scores was reported. One study also revealed no correlation with Aberdeen Varicose Vein Questionnaire improvements post-treatment. The majority of studies failed to include C0 and C1 participants. Conclusions: While further studies are required to improve the level of evidence, the existing literature suggests that truncal vein diameters correlate with clinical severity. Diameters are a poor predictor of HRQoL, with no relationship to patients' perceived impact of chronic venous disease. As such, vein diameter should not be used as a measure to decide who needs venous intervention.